Crystallization and preliminary crystallographic analysis of the chimeric protein LKB1–14‐3‐3ζ. Issue 12 (1st December 2013) - Ding, Sheng; Zhou, Ruiqing; Zhu, Yaqin
<x xml:space="preserve">Abstract</x> LKB1, a tumour suppressor, plays key roles in cell polarity, cell growth and energy metabolism. 14‐3‐3 proteins bind to LKB1 and suppress its functions. A chimera containing 14‐3‐3ζ and its binding region in LKB1 was constructed and the chimeric protein LKB1–14‐4‐3ζ was purified and crystallized. The crystal of LKB1–14‐4‐3ζ diffracted to 2.9 Å resolution and belonged to space group R32, with unit‐cell parameters a = b = 130.262, c = 264.960 Å. Structure determination and refinement are in progress.